A study on the effectiveness of fraudulent financial statements prevention & detection methods from users perspective / Rashidah Abdul Rahman, Irda Syahira Khair Anwar and Noor Faiza M. Jaafar - Abdul Rahman, Rashidah; Khair Anwar, Irda Syahira; M. Jaafar, Noor Faiza (Research Management Institute (RMI), 2012)
Bank fraud may represent one of the major causes of bankruptcy in the world. Motivated by previous bank fraud cases in India (The Ketan Parekh fraud) and in Dubai (Dubai Islamic Bank scandal), this research aims to focus on fraud in Malaysia's Islamic banks. This research is carried out to identify the common types of bank fraud that frequently happen in Islamic banks, the underlying determinants and the amount of losses as a result of fraud cases. Also, this study aims to- provide an insight on the perception of bankers towards the effectiveness of fraud prevention and detection techniques in Malaysian Islamic banks. In addition, this study aims to contribute an empirical analysis on the comparison between demographic variables such as gender, education level and working experience in banking industry towards the level of effectiveness of fraud prevention and detection techniques. The targeted respondents are among managers and officers within Islamic banks in Malaysia. Out of total the 255 questionnaires sent to the respondents, 146 responses were received, giving a response rate of 57.25%. The findings indicated the protection software/application as the most effective components of fraud prevention techniques. Meanwhile, bank reconciliation, password protection and internal control review and improvement represents as the most effective techniques when assessing independently. The results also show that there are no significant differences between gender, education level and working experience of a banker towards the level of effectiveness of fraud prevention and detection techniques. This study hopefully will benefit both academicians and practitioners in term of evaluation of the current level of protection against bank fraud in Malaysia.